Pendidikan karakter siswa di masa pandemi, siapa yang bertanggung jawab? - Ibad, Rofiul; Muhid, Abdul (Tawazun: Jurnal Pendidikan Islam, 2022)
This paper examines the person in charge of improving the understanding of character education in students during the spread of the CoronaVirus Disease-2019 virus, which requires students not to miss the lessons given as they should be. Writing that uses the Literature Review method comes from several sources, including journals, books, and supporting documents. Increasing understanding of character education is an effort to help students understand, pay attention to, and adhere to core ethical values. This study shows that the role of one component alone is not strong enough to increase the understanding of character in students, but all stakeholders, both from government policy, educators and all components in it, as well as the role of both parents, are very important in achieving student character education. during this CoronaVirus Disease-2019 pandemic. Abstrak Tulisan ini mengkaji tentang penanggung jawab peningkatan pemahaman pendidikan karakter pada siswa di masa penyebaran virus CoronaVirus Disease-2019, yang menuntut siswa untuk tidak ketinggalan pelajaran yang diberikan sebagaimana mestinya. Penulisan yang menggunakan metode Literature Review ini bersumber dari beberapa sumber antara lain jurnal, buku, dan dokumen pendukung. Peningkatan pemahaman pendidikan karakter merupakan upaya membantu peserta didik memahami, memperhatikan, dan berpegang teguh pada nilai-nilai etika inti. Penelitian ini menunjukkan bahwa peran salah satu komponen saja tidak cukup kuat untuk meningkatkan pemahaman karakter pada peserta didik, tetapi semua pemangku kepentingan, baik dari kebijakan pemerintah, pendidik dan semua komponen di dalamnya, serta peran kedua orang tua, sangat penting dalam pencapaian pendidikan karakter siswa di masa pandemi CoronaVirus Disease-2019 ini.